U–Pb ages of zircons from Mesozoic intrusive rocks in the Yanbian area, Jilin Province, NE China: Transition of the Paleo-Asian oceanic regime to the circum-Pacific tectonic regime. (1st August 2017) - Yang, Dong-Guang; Sun, De-You; Gou, Jun; Hou, Xue-Gang
Graphical abstract: Highlights: The magmatism in the Yanbian area has been subdivided into four stages. The Late Triassic intrusive rocks formed in a post-collisional extensional environment. The Early Jurassic intrusive rocks mark the beginning of the circum-Pacific tectonic regime. The transition of two tectonic regime happened during the Late Triassic to Early Jurassic. Abstract: Geology in the Yanbian area, NE China, is a key to understanding the relationship between the Paleo-Pacific tectonic regime and the older Paleo-Asian oceanic regime, especially the transition between the regimes during the Mesozoic. A compilation of 131 U–Pb zircon ages, including 18 obtained in the present study, shows that the late Paleozoic to Mesozoic magmatism in the Yanbian area took place from 285 to 105 Ma (mainly 205–160 Ma) and that there was a peak of activity at ∼175 Ma and a hiatus from the Late Jurassic to Early Cretaceous (150–130 Ma). Provisionally, we subdivide the magmatic activity into four dominant stages: Middle Permian to Middle Triassic (280–240 Ma), Late Triassic (230–205 Ma), Early to Middle Jurassic (205–160 Ma) and Early Cretaceous (130–105 Ma). Middle Permian intrusive rocks, including pyroxenite, gabbro, diorite, granodiorite, tonalite and monzogranite, are interpreted to have been emplaced along an Andean-style continental margin in association with the subduction of the Paleo-Asian oceanic plate. The Late Permian–Middle Triassic intrusive rocks are mainly quartz monzonite, monzogranite and syenogranite, and are considered to have been the result of syn-orogenic/post-collisional activities. The Late Triassic magmatism involved not only the emplacement of mafic–ultramafic intrusive rocks, but also coeval I- and A-type granitoids, indicating an extensional environment after the final closure of the Paleo-Asian Ocean. Since the Jurassic, the tectonic setting has been dominated by subduction of the Paleo-Pacific oceanic plate. Previously published data for the Yanbian area and age data from surrounding regions show that the entire region from the Yanbian area to the Korean Peninsula and the Japanese Islands experienced peaks in igneous activities that ranged from 200 to 165 Ma during the Jurassic, and 120 to 110 Ma and 90 to 65 Ma during the Cretaceous. The Jurassic intrusive rocks were emplaced mainly in the west and Cretaceous intrusive rocks in the east. In other words, there is a southeastwards younging of Mesozoic intrusive rocks that appears to have been closely associated with the evolution of the Paleo-Pacific Ocean. Taking all this into account, we conclude that the transition from the Paleo-Asian oceanic regime to the circum-Pacific tectonic regime took place during the Late Triassic to Early Jurassic.